(untitled) (Journal of Open Law, Technology & Society, 2016)
The automotive industry is moving to Free, Libre, and Open Source software (FOSS). The GPLv3 is presenting a roadblock. Specifically, GPLv3 Section 6 and the installation information, or the “anti-tivoization” clause, is the reason car makers fear the GPLv3. They want to crytographically lock their cars but fear that the GPLv3 will prevent them from doing so. They have good reason to lock their cars, but I hope they have no good reason to fear the GPLv3.